Respon Pertumbuhan Akar Beberapa Hasil Persilangan Populasi F1 Tanaman Jagung (Zea mays L.) terhadap Cekaman Besi (Fe) pada Media Kultur Hara - Hanipah Tanjung; Khairunnisa Lubis; Luthfi Aziz Mahmud Siregar (Jurnal Pertanian Tropik, 2018)
The aims of the research were to know The Root Growth Response of Some crosses F1 Corn Populations (Zea mays L.) at Iron Stress (Fe) in Medium of Nutrient Culture. This research was conducted at the greenhouse Faculty of the Agriculture University of Sumatera Utara, Medan from March to April 2017. The research used Randomized Block Design (RBD) with two using two factors i.e : F1 population (NEI 9008 x CLA 46, CLA 84 x NEI 9008, CLA 106 x NEI 9008, CLA 16 x CLA 84, and CLA 84 x P1027) and iron stress treatment (0, 50 ppm, and 100 ppm). The results showed that the F1 population had a significant effect on root-canopy weight, root volume, and root canopy ratio. Iron stress treatment with different concentrations had a significant effect on root distribution parameters, root canopy ratio, root length, and the extension of root length. The interaction between F1 population and iron stress has a significant effect on root volume character. Iron treatment with a concentration of 100 ppm can still be tolerated by the F1 population of maize crops on nutrient culture. The CLA 16 x CLA 84 populations had a better adaptation to the iron stress treatment in nutrient culture media. The CLA 16 x CLA 84 had lower stress sensitivity index value and a smaller productivity gap on root dry weight.